1999
DOI: 10.1002/(sici)1097-4644(19990615)73:4<554::aid-jcb13>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of thyroid hormones on the production of testosterone in rats

Abstract: The effects of a thyroidectomy and thyroxine (T4) replacement on the spontaneous and human chorionic gonadotropin (hCG)-stimulated secretion of testosterone and the production of adenosine 3',5'-cyclic monophosphate (cAMP) in rat testes were studied. Thyroidectomy decreased the basal levels of plasma luteinizing hormone (LH) and testosterone, which delayed the maximal response of testosterone to gonadotropin-releasing hormone (GnRH) and hCG in male rats. T4 replacement in thyroparathyroidectomized (Tx) rats re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Thyroidectomy in adult rats led to decreased secretion of testosterone and 17 b -hydroxy steroid dehydrogenase (HSD) activity ( 161 ). Leydig cells cultured from adult rats show an increase in testosterone and estrogen secretion after treatment with T 3 , under basal conditions and in response to LH ( 148 ).…”
Section: Thyroid Hormonementioning
confidence: 99%
“…Thyroidectomy in adult rats led to decreased secretion of testosterone and 17 b -hydroxy steroid dehydrogenase (HSD) activity ( 161 ). Leydig cells cultured from adult rats show an increase in testosterone and estrogen secretion after treatment with T 3 , under basal conditions and in response to LH ( 148 ).…”
Section: Thyroid Hormonementioning
confidence: 99%
“…One possibility could be the difference in the severity of induced thyroid deficiency. Thus, severe thyroid deficiency, such as that induced by thyroidectomy, may result in changes in the hypothalamic‐pituitary–testicular axis (Chandrasekhar et al, 1986; Antony et al, 1995; Chiao et al, 1999; Maran et al, 2000). Changes in LH undoubtedly would affect Leydig cell regeneration.…”
Section: Stem Leydig Cells In Adult Animalsmentioning
confidence: 99%
“…Previous studies have indicated that total thyroidectomy reduces triiodothyronine (T 3 ), thyroxin (T 4 ), insulin, prolactin, corticosterone levels and acid phosphatase activities, and increases cholesterol and glutamic oxaloacetic transaminase activities in rats (2–4). Hypothyroidism also diminishes hypothalamic gonadotropin‐releasing hormone, pituitary lutinizing hormone, follicle‐stimulating hormone, growth hormone and testicular testosterone secretions (4–6). However, all these hormonal changes have been shown to be normalized by the administration of T 4 to rats with hypothyroidism (2, 5, 6).…”
mentioning
confidence: 99%